2018
DOI: 10.1002/uog.17440
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester prediction of surgical outcome in abnormally invasive placenta using the cross‐over sign

Abstract: Objective Ultrasound assessment of the relationship between the ectopic gestational sac and the endometrial line (cross-over sign; COS) Results Sixty-eight pregnancies were included in the study. Mean estimated blood loss was higher in AIP pregnancies with COS-1 than in those with COS-2+ (P = 0.039) or COS-2− (P = 0.01). Mean number of packed red blood cell units required during or after the operation was higher in women with COS-1 compared with those with COS-2+ (P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 16 publications
2
40
0
1
Order By: Relevance
“…The importance of this classification system relies on the fact that it can be used to tailor the optimal surgical approach. Assessing the topography of placental invasion has only recently been reported in the literature . In the present study, signs of vascular invasion of the parametria, identified using color Doppler ultrasonography were reported in no images obtained at 6–9 weeks of pregnancy, in 18.1% of those obtained at 11–14 weeks, and 47.6% of those taken during both the second and third trimesters; further, the visualization of vascular invasion of the parametria was more common in patients with placenta percreta compared with placenta accreta/increate among images taken during the second and third trimesters.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The importance of this classification system relies on the fact that it can be used to tailor the optimal surgical approach. Assessing the topography of placental invasion has only recently been reported in the literature . In the present study, signs of vascular invasion of the parametria, identified using color Doppler ultrasonography were reported in no images obtained at 6–9 weeks of pregnancy, in 18.1% of those obtained at 11–14 weeks, and 47.6% of those taken during both the second and third trimesters; further, the visualization of vascular invasion of the parametria was more common in patients with placenta percreta compared with placenta accreta/increate among images taken during the second and third trimesters.…”
Section: Discussionsupporting
confidence: 42%
“…Kaelin Agten et al . showed that cesarean scar pregnancy implanted “on the scar”, defined as a placenta implanted partially or fully on top of a well healed scar, demonstrated substantially better outcomes compared with patients with the cesarean scar pregnancy implanted into the niche of a deficient or dehiscent scar, whereas Cali et al . showed that the relationship between the gestational sac of the cesarean scar pregnancy, the previous cesarean scar, and the anterior uterine wall thickness could be used to predict not only the evolution of the cesarean scar pregnancy towards the most severe types of AIP, but also clinical outcomes among these women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown recently that early first‐trimester (5–7 weeks' gestation) ultrasound assessment can predict the possibility of developing PAS disorder in women at high risk for this anomaly, thus supporting the role of early sonographic evaluation as a potential early predictor of this complication.…”
Section: Introductionmentioning
confidence: 87%
“…Early first‐trimester ultrasound images, obtained between 5 and 7 weeks of gestation, were retrieved from the computerized database of each referring hospital. The relationship between the position of the gestational sac and the prior Cesarean scar (CS) was assessed according to three sonographic markers reported by Calí et al . (the crossover sign (COS)), Kaelin Agten et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation